Anti-Malarial Chemoprophylaxis Following Evacuation from Afghanistan. Issue 1 (1st March 2012) - Keene, DD; Tong, JL; Roughton, S; Fadden, SJ
Abstract : UK forces deployed to Afghanistan between March and November are prescribed anti-malarial chemoprophylaxis (AMC). In 2007 an audit showed poor pre-injury AMC compliance and a prescription rate of 50% amongst those casualties evacuated to Role 4. We re-audited the post-deployment AMC prescribing practice for casualties from Afghanistan for the 2008 and half of the 2009 malaria season. Using the Role 4 prescribing information and communication system (PICS), a retrospective AMC search for Proguanil, Chloroquine, Doxycycline, Mefloquine and Malarone was performed on these casualties. Only five out of 305 (1.64%) inpatients were prescribed appropriate post-deployment AMC medication. Awareness of the need to prescribe AMC following evacuation remains poor, and may be improved by recording AMC compliance in field medical records and modifying the PICS software.